Conference Report: Cerebellar Development and Disease at Single-Cell Resolution - Lena M. Kutscher; Davide Aprile; N. Sumru Bayin; Esther B. E. Becker; Valentina Cerrato; Giacomo Turrini; Marion Coolen; Vincent Cantagrel; Béatrice C. Durand; Myron K. Evans II; Parthiv Haldipur; Kathleen J. Millen; et al. (The Cerebellum, 2025)

Controls on Water-Column Respiration Rates in a Coastal Plain Estuary: Insights from Long-Term Time-Series Measurements - David Prichett; Joan M. Bonilla Pagan; Casey L. S. Hodgkins; Jeremy M. Testa (Estuaries and Coasts, 2024)

Controls on Oxygen Variability and Depletion in the Patuxent River Estuary - Allison Dreiss; Amir Reza Azarnivand; Anna Hildebrand; Seyedeh Fardis Pourreza Ahmadi; Syeda Sadia Ali; Veronica Malabanan Lucchese; Qian Zhang; Laura L. Lapham; Ryan J. Woodland; Lora Harris; Jeremy M. Testa (Estuaries and Coasts, 2024)
Oxygen depletion in coastal waters is increasing globally due primarily to eutrophication and warming. Hypoxia responses to nutrient loading and climate change have been extensively studied in large systems like the Chesapeake Bay and the Baltic Sea, while fewer studies have investigated smaller, shallower hypoxic zones. Thus, an improved understanding of the interactions of eutrophication and warming on hypoxia expansion (or reduction) in the wide variety of different estuarine environments is needed. We examined interannual controls on oxygen depletion in the Patuxent River estuary, a eutrophic sub-estuary of Chesapeake Bay where seasonal hypoxia develops annually. We conducted a spatial and temporal analysis of dissolved oxygen (DO) trends, timing, and several metrics of depletion over a long-term record (1985–2021). We found an internally generated hypoxic zone that initiates in the middle estuary, spreading upstream and downstream as the summer progresses, and that hypoxic volume days (HVD) have been increasing (0.11 per year, p = 0.03) over the record despite reduced watershed nitrogen loads and stable phosphorus loads. River flow and temperature have been increasing and are major drivers of increased HVD, with river flow explaining 40% of the interannual variation in HVD (temperature has increased 0.03 and 0.06 °C per year in summer and fall, respectively). Apparent oxygen utilization (AOU) is increasing in bottom waters in the fall, consistent with increasing trends of both water temperature and stratification strength. HVD was negatively related ( r 2 = 0.34, slope = −0.59*HVD) to the biomass of benthic invertebrates in the middle region of the estuary, suggesting that benthic forage for higher trophic levels will be limited by sustained hypoxia. These results indicate that current and future climate variability plays an important role in regulating oxygen depletion in the Patuxent River estuary, which reinforces the need to factor climate change into strategies for the restoration and management of estuaries.

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

P06-20 OMICs approaches linking effects of endocrine disrupters on developing rat hippocampus with impaired memory function in adult offspring and human stem cell-derived in vitro models - W. Lichtensteiger; C. Bassetti-Gaille; H. Rehrauer; N. Caporale; B. Linillos Pradillo; L. Rancan; H. Idrissi; L. Miguélez-Salas; J. Felix; S.D. Paredes; S. Evangelista; M. de la Fuente; et al. (Toxicology Letters, 2024)

Large-Scale Spatial and Temporal Patterns and Importance of Sediment–Water Oxygen and Nutrient Fluxes in the Chesapeake Bay Region - W. R. Boynton; M. A. C. Ceballos; C. L. S. Hodgkins; D. Liang; J. M. Testa (Estuaries and Coasts, 2023)

Biogeochemical states, rates, and exchanges exhibit linear responses to large nutrient load reductions in a shallow, eutrophic urban estuary - Jeremy M. Testa; Walter R. Boynton; Casey L. S. Hodgkins; Amanda L. Moore; Eva M. Bailey; Johanna Rambo (Limnology and Oceanography, 2022)
We examined responses of water‐column conditions, sediment‐water fluxes, ecosystem metabolism, and nutrient export in the Back River estuary during the past three decades following multiple phases of nutrient load reductions from a large wastewater treatment plant. Total nitrogen (TN) loads from the treatment plant declined from 7000 kg N d −1 in the mid‐1980s to 1500 kg N d −1 following the implementation of enhanced nutrient removal in late 2017. Total phosphorus (TP) loads declined by ~90% from peaks in the mid‐1980s–1990s and have been stable ever since. In response, TN and TP concentrations measured since 1985 show declines that generally mirror that of loads from the treatment plant, and box model computations suggest significant reductions in nutrient export to adjacent Chesapeake Bay. As a consequence, water‐column chlorophyll a (Chl a ) concentrations have declined modestly over the record, despite inter‐annual variability. This reduction in Chl a coincided with a reduced frequency of nitrogen and phosphorus concentrations that would saturate phytoplankton growth, as well as reductions in ecosystem gross primary production and respiration derived from high‐frequency oxygen time‐series. Sediment‐water fluxes of dissolved nitrogen, phosphorus, and oxygen, as well as associated sediment concentrations of nitrogen, phosphorus, and carbon also declined over the record. These temporal patterns were reproduced in a 35‐yr model simulation that suggests a relatively rapid response to reduced organic matter deposition changes. Finally, the recycling of ammonium for a given TN load declined substantially, consistent with high observed rates of denitrification, indicating that well‐mixed estuaries can recover relatively rapidly in response to nutrient remediation.

Spatiotemporal variability of light attenuation and net ecosystem metabolism in a back-barrier estuary - Neil K. Ganju; Jeremy M. Testa; Steven E. Suttles; Alfredo L. Aretxabaleta (Ocean Science, 2020)
Quantifying system-wide biogeochemical dynamics and ecosystem metabolism in estuaries is often attempted using a long-term continuous record at a single site or short-term records at multiple sites due to sampling limitations that preclude long-term monitoring. However, differences in the dominant primary producer at a given location (e.g., phytoplankton versus benthic producers) control diel variations in dissolved oxygen and associated ecosystem metabolism, and they may confound metabolic estimates that do not account for this variability. We hypothesize that even in shallow, well-mixed estuaries there is strong spatiotemporal variability in ecosystem metabolism due to benthic and water-column properties, as well as ensuing feedbacks to sediment resuspension, light attenuation, and primary production. We tested this hypothesis by measuring hydrodynamic properties, biogeochemical variables (fluorescent dissolved organic matter – fDOM, turbidity, chlorophyll a fluorescence, dissolved oxygen), and photosynthetically active radiation (PAR) over 1 year at 15 min intervals at paired channel (unvegetated) and shoal (vegetated by eelgrass) sites in Chincoteague Bay, Maryland–Virginia, USA, a shallow back-barrier estuary. Light attenuation (KdPAR) at all sites was dominated by turbidity from suspended sediment, with lower contributions from fDOM and chlorophyll a. However, there was significant seasonal variability in the resuspension–shear stress relationship on the vegetated shoals, but not in adjacent unvegetated channels. This indicated that KdPAR on the shoals was mediated by submerged aquatic vegetation (SAV) and possibly microphytobenthos presence in the summer, which reduced resuspension and therefore KdPAR. We also found that gross primary production (Pg) and KdPAR were significantly negatively correlated on the shoals and uncorrelated in the channels, indicating that Pg over the vegetated shoals is controlled by a feedback loop between benthic stabilization by SAV and/or microphytobenthos, sediment resuspension, and light availability. Metabolic estimates indicated substantial differences in net ecosystem metabolism between vegetated and unvegetated sites, with the former tending towards net autotrophy in the summer. Ongoing trends of SAV loss in this and other back-barrier estuaries suggest that these systems may also shift towards net heterotrophy, reducing their effectiveness as long-term carbon sinks. With regards to temporal variability, we found that varying sampling frequency between 15 min and 1 d resulted in comparable mean values of biogeochemical variables, but extreme values were missed by daily sampling. In fact, daily resampling minimized the variability between sites and falsely suggested spatial homogeneity in biogeochemistry, emphasizing the need for high-frequency sampling. This study confirms that properly quantifying ecosystem metabolism and associated biogeochemical variability requires characterization of the diverse estuarine environments, even in well-mixed systems, and demonstrates the deficiencies introduced by infrequent sampling to the interpretation of spatial variability.

Oxygen and Nutrient Exchanges at the Sediment-Water Interface: a Global Synthesis and Critique of Estuarine and Coastal Data - W. R. Boynton; M. A. C. Ceballos; E. M. Bailey; C. L. S. Hodgkins; J. L. Humphrey; J. M. Testa (Estuaries and Coasts, 2018)

Progress and Challenges in Coupled Hydrodynamic-Ecological Estuarine Modeling - Neil K. Ganju; Mark J. Brush; Brenda Rashleigh; Alfredo L. Aretxabaleta; Pilar del Barrio; Jason S. Grear; Lora A. Harris; Samuel J. Lake; Grant McCardell; James O’Donnell; David K. Ralston; Richard P. Signell; et al. (Estuaries and Coasts, 2016)

Life history and population dynamics of southern Alaska resident killer whales ( Orcinus orca ) - Craig O. Matkin; J. Ward Testa; Graeme M. Ellis; Eva L. Saulitis (Marine Mammal Science, 2014)
Resident (fish eating) killer whales (Orcinus orca ) in the North Pacific have been the subject of long‐term studies in several geographical regions. The current study examines population parameters in the southern Alaska resident population from 1984 to 2010 and develops a population model. The southern Alaska resident population ranges from southeastern Alaska through the Kodiak archipelago and contains over 700 individuals. We follow the life histories of 343 identifiable whales in 10 pods from two clans born before and during the study. Population parameters were comparable to those of the British Columbia northern resident population during the 1970s and 1980s, except that age of maturity was approximately one year earlier. The average annual rate of increase was slightly higher in Alaska (3.5%) than for the British Columbia northern residents (2.9%) and probably represents a population at r‐max (maximum rate of growth). Reasons for the high growth rate in Alaska could be a recovery following past anthropogenic mortalities, or more likely, a response to increasing salmon returns in recent decades, resulting in an increase in carrying capacity. The slow maturation and low rate of reproductive response makes these whales slow to recover from natural or anthropogenic catastrophes.

Role of spiramycin/cotrimoxazole association in the mother-to-child transmission of toxoplasmosis infection in pregnancy - P. Valentini; M. L. Annunziata; D. F. Angelone; L. Masini; M. Santis; A. Testa; R. L. Grillo; D. Speziale; O. Ranno (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

Role of spiramycin/cotrimoxazole association in the mother-to-child transmission of toxoplasmosis infection in pregnancy - P. Valentini; M. L. Annunziata; D. F. Angelone; L. Masini; M. De Santis; A. Testa; R. L. Grillo; D. Speziale; O. Ranno (European Journal of Clinical Microbiology & Infectious Diseases, 2009)

A 169-base pair tandem repeat DNA marker for subtelomeric heterochromatin and chromosomal rearrangements in aphids of the Myzus persicae group - Jennifer M. Spence; Roger L. Blackman; Johann M. Testa; Paul D. Ready (Chromosome Research, 1998)

Insulin reduces HBsAg production by PLC/PRF/5 human hepatoma cell line - M. Clementi; I. Testa; P. Bagnarelli; A. Festa; P. Pauri; M. Brugia; L. Calegari; C. de Martinis (Archives of Virology, 1984)